2020
DOI: 10.1158/1078-0432.ccr-20-0369
|View full text |Cite
|
Sign up to set email alerts
|

Valganciclovir as Add-on to Standard Therapy in Glioblastoma Patients

Abstract: Purpose: Several groups have reported a prevalence of human cytomegalovirus (CMV) in glioblastoma close to 100%. Previously, we reported that treatment with the antiviral drug valganciclovir as an add-on to standard therapy significantly prolonged survival in 50 patients with glioblastoma. Here, we present an updated retrospective analysis that includes an additional 52 patients.Experimental Design: From December 2006 to November 2019, 102 patients with newly diagnosed glioblastoma received valganciclovir as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…While awaiting a possibility to find financial support for a randomized trial, the number of valganciclovir-treated patients increased to 139 patients by 2019. Among these, 102 had primary glioblastoma, and the median OS rate was very similar to that in the first trial: 24.1, versus 13.3 months in 231 contemporary control patients ( p < 0.0001) [ 14 ]. Both patients with methylated MGMT and those with an unmethylated MGMT promoter showed potential benefit from valganciclovir treatment.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While awaiting a possibility to find financial support for a randomized trial, the number of valganciclovir-treated patients increased to 139 patients by 2019. Among these, 102 had primary glioblastoma, and the median OS rate was very similar to that in the first trial: 24.1, versus 13.3 months in 231 contemporary control patients ( p < 0.0001) [ 14 ]. Both patients with methylated MGMT and those with an unmethylated MGMT promoter showed potential benefit from valganciclovir treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Since 2006, we have treated 139 patients with glioblastoma with valganciclovir as an add-on to standard therapy; this drug treatment aims to target the negative effects of CMV in glioblastoma, an infection that is present in the majority of these tumors. We recently reported a retrospective data analysis demonstrating enhanced survival among 102 patients with primary glioblastoma who received valganciclovir as an add-on to standard therapy compared with 231 control patients [ 14 ]. Here, we also report that eight patients with secondary glioblastoma who were treated with valganciclovir as an add-on to second-line therapy survived significantly longer than controls after their progression to glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the wide presence of HCMV in different tumor types, this virus may represent a potential target of therapy for HCMV positive malignancies, including breast cancer. Retrospective clinical trials have shown that antiviral therapy with valganciclovir as an add on to standard therapy seems to improve survival in patients with glioblastoma [ 44 , 45 ], and also dendritic cells vaccination shows promising results in these patients [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Furthermore, antiviral treatment of glioblastoma patients has indicated a prolonged overall survival. 9 This virus is reactivated by inflammation and promotes inflammation to secure its own existence, and a link has been proposed between HCMV, inflammation and cancer.…”
Section: Introductionmentioning
confidence: 99%